Letter to John V. Tunney from Jane Tolmach and Adele Leopold - Jane Tolmach::::::; Adele Leopold:::::: (1971)
In this January 1, 1971 letter, Jane Tolmach and Adele Leopold invite Senator John V. Tunney to serve as the main speaker at the Key Women Award Party on January 16, 1971, at the Beverly Hilton in Los Angeles. The event honors women volunteers who supported Democratic nominees in the 1970 campaign, and Tunney's recent election is described as especially significant. They express hope that he and his wife will attend and send best wishes for his new role.